Assessing web site usability measurement - Nur Sukinah, Aziz; Adzhar, Kamaludin; Norrozila, Sulaiman (eSAT Publishing House Pvt. Ltd., 2013)
Web evaluation has been used in decade to validate the web site to see how it performs. When analysing a web site, typical factors to be considered are the way the information is organized and presented, and how to access and navigate the informative structure. Usability evaluations evaluate the ease of use of a web site functions and see either the user can perform their tasks efficiently. This paper review existing usability standards and models in determining an appropriate model for evaluating the usability of web site. Previous research are reviewed and comparison and analysis of existing usability model and identification of usability criteria and characteristics for web site is made to identify the attribute or characteristic that should be used in evaluating web site.This study proposed an extension of the QUIM model as a basic model for usability model for a web site. Therefore, a set of guidelines to assist in determining design and usability